Human papillomavirus genotyping using HPV DNA chip analysis in Korean women. Issue 2 (1st February 2007) - Lee, H. S.; Kim, K. M.; Kim, S. M.; Choi, Y. D.; Nam, J. H.; Park, C. S.; Choi, H. S.
Abstract : This study was designed to investigate the genotypes of human papillomavirus (HPV) in Korean women who had abnormal cervical cytology and to evaluate the clinical accuracy of HPV DNA chip analysis for the diagnosis of cervical neoplasia. Liquid-based cytology preparations, HPV DNA chip analysis, and cervical biopsy were performed in 2358 women. High-risk HPV was identified in 23.5% of 1650 histologically confirmed normal samples (including cervicitis and squamous metaplasia) and in 81.8% of 708 samples with cervical intraepithelial neoplasia (CIN) and carcinoma ( P < 0.01). The major prevalent high-risk HPV genotypes in 381 samples of CIN II/III were HPV-16, -58, -33, and -31, in order of prevalence rate (average overall, 78.0%), and HPV-16, -18, -58, and -33 (average overall, 81.2%) in 133 samples of squamous cell carcinoma (SCC). The infection rate of HPV-16 was significantly higher than that of other high-risk HPV genotypes in all normal, CIN, and SCC cases ( P < 0.01) and increased with more advanced squamous cervical lesions ( P < 0.01). The detection accuracy of high-risk HPV using HPV DNA chip analysis for CIN II or worse was as follows: sensitivity 84% (81–87%), specificity 72% (70–74%), positive predictive value 47% (44–50%), and negative predictive value 94% (92–95%). These results suggest that HPV DNA chip analysis may be a reliable diagnostic tool for the detection of cervical neoplasia and that there are geographic differences in the distribution of high-risk HPV genotypes.